BERSEDEKAH DI ERA PANDEMI: KONTRIBUSI LAZISMU KOTA DEPOK TERHADAP FENOMENA WABAH COVID-19 TAHUN 2020-2022 M - Alfawwaz, Muhammad Fariz; Agus Permana; Dani Wardani (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2024)
The Covid-19 pandemic has triggered a spike in poverty rates, making many people need assistance both through the government and private institutions. Zakat management institutions, as Islamic philanthropic institutions, have a responsibility to help ease the burden on communities affected by the pandemic. Lazismu Depok City has shown a very important role in efforts to ease the burden on communities affected by Covid-19, especially among the Muslim community around the Depok City area during 2020-2022. This research aims to understand and analyze the effectiveness of Lazismu Depok City in distributing aid during the Covid-19 pandemic. Researchers use historical research methods through four stages, namely heuristics, criticism, interpretation and historiography by utilizing information through documentary and oral sources. The results of this research show that Lazismu Depok City shows good adaptability in facing the challenges of the Covid-19 pandemic. Lazismu Depok City is also developing various innovative programs to provide wider, more sustainable benefits, and is developing various innovative programs to provide wider and more sustainable benefits during the Covid-19 pandemic.